(untitled) (Scientific journal of the Fergana State University, 2025)
This study analyzes the importance of developed methods for effectively conducting physical education lessons in rural schools under high-temperature conditions. A pedagogical experiment examined the impact of static gymnastics and breathing exercises on students’ physical fitness. The results demonstrated improved mobility and physical strength during the exercises.